2019
DOI: 10.1088/1755-1315/355/1/012077
|View full text |Cite
|
Sign up to set email alerts
|

Waterflow in the Paddy Field Installed with Sheetpipe Mole Drains

Abstract: Sheet-pipe is a sort of perforated mole drain placed horizontally between 30–50 cm below the land surface commonly having a water-logged problem. The sheet-pipe can be installed with a heavy machine mole drainer. The primary purpose of installing sheet-pipe is to maintain or control the expected water table in farmlands. Sheet-pipe having a diameter of 5 mm has been installed at a depth of 40 cm with a drain spacing of 4 m and length of 100 m covering a paddy field of 1 hectare located in Sukamandi District, S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 13 publications
0
7
0
Order By: Relevance
“…Sheet-pipe system drained water properly as indicated by lower water depth in the SP field than that in the NSP field during the planting period, as shown in Figure 6. A previous study reported that the sheet-pipe system drained water two times faster than the NSP field [25]. The water depth trends in both fields were identical that pointed out irrigation water was supplied at a similar rate and in total (Table 2).…”
Section: Water Balance In Both Fieldsmentioning
confidence: 57%
See 2 more Smart Citations
“…Sheet-pipe system drained water properly as indicated by lower water depth in the SP field than that in the NSP field during the planting period, as shown in Figure 6. A previous study reported that the sheet-pipe system drained water two times faster than the NSP field [25]. The water depth trends in both fields were identical that pointed out irrigation water was supplied at a similar rate and in total (Table 2).…”
Section: Water Balance In Both Fieldsmentioning
confidence: 57%
“…A sheet-pipe system is possibly used as subsurface drainage technology with more efficiency and cost without digging the soil along the drainage pipes channel. Sheet-pipe typed is commonly installed 30-50 cm below the soil surface and placed horizontally by a machine called a mole drainer, then the sheets will automatically be a perforated pipe [25]. In 2018, this technology was introduced in Indonesia and, firstly, installed in the paddy field belong to the Indonesian Center for Rice Research, Sukamandi West Java.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, water table reduction and increases in air-filled capacity, saturated hydraulic conductivity, and water-holding capacity were studied other conventional drains, sheet pipe has one significant advantage of not requiring transitional materials (JASPiP 2014) such as gravel and straw; thus, sheet pipe is considered a cost-effective and environmentally friendly technique. The limited previous studies on paddy fields with heavy texture soils found that installing sheet pipe had some benefits in reducing waterlogging and the electrical conductivity (EC) of drained water (Setiawan et al 2019). Moreover, our previous study reported the long-term impacts of sheet pipe on some paddy fields (Soe et al 2019).…”
Section: Introductionmentioning
confidence: 92%
“…Rice fields with sheet pipe installation can be drained more quickly than those without using sheet pipes. As soon as rain occurs, the water is immediately infiltrated at a parabolic rate up to 0.94 cm/h, higher than the standard steady-state infiltration rate of 0.121 cm/h, to facilitate its management to provide aerobic and anaerobic conditions [3].…”
Section: Introductionmentioning
confidence: 99%